The Changing Face of Hemostasis Testing in Modern Laboratories: Consolidation, Automation, and Beyond - Lippi, Giuseppe; Plebani, Mario; Favaloro, Emmanuel J. (Seminars in Thrombosis and Hemostasis, 2015)
The reality of laboratory diagnostics as a whole, and hemostasis testing in particular, is evolving under new paradigms of efficiency. The driving forces of health care and laboratory diagnostics in the third millennium are mainly represented by macro- and microeconomics. In a world with limited resources, shattered by an unprecedented economic crisis, laboratory diagnostics is undergoing a substantial reorganization, with emergence of new models under the imperative of terms, such as bedside testing, consolidation, and networking. The paradigms under which these changes are being developed include a variety of environment, preanalytical, technological, professional, and health-care aspects. The maintenance of continued quality is indeed the major challenge to be faced in the foreseeable future. In fact, some challenges prepotently emerge during a consolidation process, which basically involve delayed testing, centrifugation, transportation, and stability of the specimens, as well as the potential mismatch of sample matrix. This article is aimed to provide an overview of the current economic scenario of laboratory diagnostics and discuss the changing face of hemostasis testing in modern laboratories, providing a synthetic overview about potential drawbacks of actualized solutions.
Keywords: laboratory diagnostics; hemostasis testing; consolidation; automation; quality; pre-analytical variability